Evaluation as a process of teacher (trans)formation - Sousa, Aurineide Amaro de; Oliveira, Evandro Nogueira de (Research, Society and Development, 2023)
This study explores the importance of learning assessment in teacher education and its contribution to the educational transformation process. In this sense, large-scale assessments are seen as guiding public policies, using the information obtained to improve institutions. However, it should be recognized that assessment is not limited to objective or subjective aspects. The objective of this study was to investigate the role of learning assessment in the context of teacher education. To this end, a theoretical discussion based on a literature review was conducted. The findings indicate that in order to improve teaching practice, it is necessary to establish robust mechanisms for teacher education. Additionally, it is crucial to explore a broad and diversified approach to assessment, considering both quantitative results and qualitative aspects of the educational process. Therefore, there is a need to use assessment results for decision-making and to develop effective educational policies. The importance of reflective and critical assessment is emphasized to enhance the effectiveness of assessment as a tool for improving the educational process, aiming for a fair and inclusive assessment system that promotes teachers’ professional development. Ongoing dialogue among educators, administrators, and other stakeholders in the field of education is essential to achieve quality education that meets the needs of contemporary society.